2019
DOI: 10.1021/acs.macromol.9b01712
|View full text |Cite
|
Sign up to set email alerts
|

Chain and Ion Dynamics in Precise Polyethylene Ionomers

Abstract: We analyze the dynamics from microsecond-long, atomistic molecular dynamics (MD) simulations of a series of precise poly­(ethylene-co-acrylic acid) ionomers neutralized with lithium, with three different spacer lengths between acid groups on the ionomers and at two temperatures. At short times, the intermediate structure factor calculated from the MD simulations is in reasonable agreement with quasi-elastic neutron scattering data for partially neutralized ionomers. For ionomers that are 100% neutralized with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 42 publications
(104 reference statements)
1
51
0
Order By: Relevance
“…Previous work has shown that the addition of salt slows down the polymer dynamics on these timeand length-scales. 8,[12][13][14] The QENS data are used to determine the effect of added salt on the monomeric friction coefficient in both PCEA-and PEObased electrolytes. We explore the relationships between this parameter and ionic conductivity in the two systems.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that the addition of salt slows down the polymer dynamics on these timeand length-scales. 8,[12][13][14] The QENS data are used to determine the effect of added salt on the monomeric friction coefficient in both PCEA-and PEObased electrolytes. We explore the relationships between this parameter and ionic conductivity in the two systems.…”
Section: Introductionmentioning
confidence: 99%
“…The subject of ionic conductivity in polymeric materials with heterogeneous structures is of intense current interest, primarily due to the societal need for better battery alternatives. Significant progress has recently been made toward formulating polymeric materials with enhanced ionic conductivities and at the same time not compromising on their mechanical stability. The procedures that have been implemented in this endeavor are primarily experiments and simulations. Generally speaking, the investigated systems include solid polymer electrolytes such as salt-doped poly­(ethylene oxide), polymeric single-ion conductors, polymerized ionic liquids, and polyelectrolyte solutions in nanocapillaries. …”
mentioning
confidence: 99%
“…3,[7][8][9][10] In these cases, the translation of ions can be accommodated by segmental relaxation of the polymer chains. 11,12,21,[13][14][15][16][17][18][19][20] Thus, ionic conductivity of a well-studied polymer electrolyte, a mixture of poly(ethylene oxide) (PEO) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) salt measured by ac impedance spectroscopy, can be explained entirely by the segmental relaxation quantified by quasi-elastic neutron scattering (QENS). 14 To our knowledge, no attempt has been made to study the relaxation processes that govern polymer electrolytes under large applied potentials.…”
mentioning
confidence: 99%
“…A popular approach for characterizing ion transport in electrolytes is ac impedance spectroscopy, which reflects the oscillation of ions in response to a small ac potential. ,, Another popular approach is pulse-field gradient NMR, wherein the Brownian motion of ions is quantified in the absence of an applied potential. , In these cases, the translation of ions can be accommodated by segmental relaxation of the polymer chains. Thus, ionic conductivity of a well-studied polymer electrolyte, a mixture of poly­(ethylene oxide) (PEO) and lithium bis­(trifluoromethanesulfonyl)­imide (LiTFSI) salt measured by ac impedance spectroscopy, can be explained entirely by the segmental relaxation quantified by quasi-elastic neutron scattering (QENS) . To our knowledge, no attempt has been made to study the relaxation processes that govern polymer electrolytes under large applied potentials.…”
mentioning
confidence: 99%
See 1 more Smart Citation